Association of hepatitis C virus genotype 2 spread with historic slave trade and commerce routes in Western Africa. Issue 2 (21st July 2022) - Postigo-Hidalgo, Ignacio; Magassouba, N'Faly; Soropogui, Barré; Fichet-Calvet, Elisabeth; Drexler, Jan Felix
Abstract: The hepatitis C virus genotype 2 (HCV2) is endemic in Western and Central Africa. The HCV2 evolutionary origins remain uncertain due to the paucity of available genomes from African settings. In this study, we investigated the molecular epidemiology of HCV infections in rural Guinea, Western Africa, during 2004 and 2014. Broadly reactive nested reverse transcription polymerase chain reaction (RT-PCR)-based screening of sera from 1, 571 asymptomatic adults resulted in the detection of 25 (1.5 per cent; 95 per cent confidence interval 0.9–2.3) positive samples, with a median viral load of 2.54E + 05 IU/ml (interquartile range 6.72E + 05). HCV-infected persons had a median age of 47 years, and 62.5 per cent were male and 37.5 per cent were female. The full polyprotein-encoding genes were retrieved by a combination of high throughput and Sanger sequencing from 17 samples showing sufficiently high viral loads. Phylogenetic analysis and sequence distances ≥13 per cent averaged over the polyprotein genes compared to other HCV2 subtypes revealed nine previously unknown HCV2 subtypes. The time to the most recent common ancestor of the Guinean HCV2 strains inferred in a Bayesian framework was 493 years (95 per cent Highest posterior density (HPD) 453–532). Most of the Guinean strains clustered poorly by location on both the level of sampling sites within Guinea and the level of countries in the phylogenetic reconstructions. Ancestral state reconstruction provided decisive support (Bayes factor > 100) for an origin of HCV2 in Western Africa. Phylogeographic reconstructions in a Bayesian framework pointed to a radial diffusion of HCV2 from Western African regions encompassing today's countries like Ghana, Guinea Bissau, or Burkina Faso, to Central and Northern African regions that took place from the 16th century onwards. The spread of HCV2 coincided in time and space with the main historic slave trade and commerce routes, supported by Bayesian tip-association significance testing (P   = 0.01). Our study confirms the evolutionary origins of HCV2 in Western Africa and provides a potential link between historic human movements and HCV2 dispersion.